Where do winds drive the Antarctic Circumpolar Current? - Allison, L; Johnson, H; Marshall, D; Munday, D (American Geophysical Union, 2010)
The strength of the Antarctic Circumpolar Current (ACC) is believed to depend on the westerly wind stress blowing over the Southern Ocean, although the exact relationship between winds and circumpolar transport is yet to be determined. Here we show, based on theoretical arguments and a hierarchy of numerical modeling experiments, that the global pycnocline depth and the baroclinic ACC transport are set by an integral measure of the wind stress over the path of the ACC, taking into account its northward deflection. Our results assume that the mesoscale eddy diffusivity is independent of the mean flow; while the relationship between wind stress and ACC transport will be more complicated in an eddy-saturated regime, our conclusion that the ACC is driven by winds over the circumpolar streamlines is likely to be robust.